PsART-ID inception cohort: clinical characteristics, treatment choices and outcomes of patients with psoriatic arthritis - DURUÖZ, MEHMET TUNCAY (OXFORD UNIV PRESS, 2021)
Objectives. Our aim is to understand clinical characteristics, real-life treatment strategies, outcomes of early PsA patients and determine the differences between the inception and established PsA cohorts. Methods. PsArt-ID (Psoriatic Arthritis- International Database) is a multicentre registry. From that registry, patients with a diagnosis of PsA up to 6 months were classified as the inception cohort (n=388). Two periods were identified for the established cohort: Patients with PsA diagnosis within 5-10 years (n = 328), >= 10 years (n = 326). Demographic, clinical characteristics, treatment strategies, outcomes were determined for the inception cohort and compared with the established cohorts. Results. The mean (S.D.) age of the inception cohort was 44.7 (13.3) and 167/388 (43.0%) of the patients were male. Polyarticular and mono-oligoarticular presentations were comparable in the inception and established cohorts. Axial involvement rate was higher in the cohort of patients with PsA >= 10 years compared with the inception cohort (34.8% vs 27.7%). As well as dactylitis and nail involvement (P = 0.004, P = 0.001 respectively). Both enthesitis, deformity rates were lower in the inception cohort. Overall, 13% of patients in the inception group had a deformity. MTX was the most commonly prescribed treatment for all cohorts with 10.7% of the early PsA patients were given anti-TNF agents after 16 months. Conclusion. The real-life experience in PsA patients showed no significant differences in the disease pattern rates except for the axial involvement. The dactylitis, nail involvement rates had increased significantly after 10 years from the diagnosis and the enthesitis, deformity had an increasing trend over time.
Keywords: psoriatic arthritis; inception cohort; early disease; DISEASE-ACTIVITY; JOINT DISEASE; RECOMMENDATIONS; MULTICENTER; PROGRESSION; CRITERIA; REGISTRY